2008
DOI: 10.1007/bf03246147
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of silver ion from aqueous solutions using conducting electroactive polymers

Abstract: In this research polypyrrole (PPy) and polyaniline (PAni) conducting polymers which were synthesized chemically on the surface of wood sawdust (SD). These electroactive polymers as coated form on sawdust then were used for sorption or removal of silver ion from aqueous solutions under simple open circuit conditions. The effects of some important parameters such as pH, initial concentration, sorbent dosage, and contact time on uptake of silver ion were also investigated in this research. The experiments were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…In the case of P3MTh/SD, sorption capacity of silver ion was much higher than SD and even higher than sawdust coated by PAni and PPy as we have previously reported. 13 The proposed mechanism for removal of silver ion employing our currently introduced adsorbent may be ionic, chelation, redox reactions. Higher sorption of silver ion by P3MTh/SD can also be explained using Pearson hard-soft acidbase theory.…”
Section: Effect Of Initial Concentrationmentioning
confidence: 99%
See 3 more Smart Citations
“…In the case of P3MTh/SD, sorption capacity of silver ion was much higher than SD and even higher than sawdust coated by PAni and PPy as we have previously reported. 13 The proposed mechanism for removal of silver ion employing our currently introduced adsorbent may be ionic, chelation, redox reactions. Higher sorption of silver ion by P3MTh/SD can also be explained using Pearson hard-soft acidbase theory.…”
Section: Effect Of Initial Concentrationmentioning
confidence: 99%
“…This might be due to the stronger interactions between sulfur atoms (in PTh) and silver ions compared to NAH groups in PPy or PAni. 13 …”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Recently, we have found that polypyrrole and polyaniline conducting electroactive polymers (CEPs) can be employed for removal of some toxic metal ions from aqueous solutions [5,6]. Synthesis of these reactive and functional polymers have been carried out by either electropolymerization at a conductive substrate (electrode) through the application of an external potential, or chemical polymerization in solution by the use of a chemical oxidant [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%